PENGARUH MODEL PEMBELAJARAN EVERYONE IS A TEACHER HERE (ETH) DENGAN BANTUAN ICE BREAKING TERHADAP LITERASI NUMERASI MATEMATIKA SISWA SMP NEGERI 31 MEDAN - Bonifasia Gultom; Israil Sitepu; Sinta Dameria Simanjuntak (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This study was conducted with the aim of determining the influence of the Everyone is a Teacher Here learning model with the help of ice breaking on students' mathematical numeracy literacy and to find out the average numeracy literacy ability taught with the Everyone is a Teacher Here (ETH) learning model with the help of ice breaking whether it is higher than using conventional learning on comparison material in grade VII SMP Negeri 31 Medan. This type of research is quantitative with quasi experimental design. These results show that H1 has an influence on the Everyone is a Teacher Here (ETH) learning model with the help of ice breaking on students' mathematical numeracy literacy, judging from the t test showing sign results. (2 tailed) of 0.01 < 0.05. The H2 test has no effect of ice breaking on students' mathematical numeracy literacy, judging from the t test shows the results of sign.(2 tailed) of 0.07 > 0.05. As for H3, there is an influence of the Everyone is a Teacher Here (ETH) learning model with the help of ice breaking on students' mathematical numeracy literacy, judging from the f test obtained sign. (tailed) by 0.00 < 0.05. In the N-Gain Score test, Ha is accepted, namely the increase in numeracy literacy taught with the Everyone is a Teacher Here (ETH) learning model with the help of ice breaking higher than students who obtain conventional learning, with an average N-Gain Score in the experimental class of 0.71 > an average N-Gain Score in the control class of 0.41.